OVERVIEWING EAST JAVA’S MARITIME ECONOMIC POTENTIAL: INPUT-OUTPUT ANALYSIS - Gisty Ajeng Septami; Pyan Putro Surya Amin Muchtar; Irfan Teguh Prima (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2017)
East Java marine resources play important role as development assets and have enormous opportunities for generating economic growth. The main potential includes 11 subsectors reinforced by the role of this province as a center of logistics and connectivity of the Eastern Indonesia Region (KIT). Realizing such potential, both central and local governments intensively attract investors to invest funds into the maritime sector in East Java. The study also attempts to deliberate the impact of investment in the maritime sector on the East Java economy in particular and Indonesia in general. The impact includes economic growth, society’s welfare, and employment. This study uses Input-Output Table of East Java Province 2008 published by the Central Bureau of Statistics (BPS). The data is quantitatively employed to find the linkage and impact multiplier of the investment. The results of this study indicate that the investment in the maritime sector induces economic growth of East Java by 11%, which also rises people income and employment rate. With the contribution of East Java to the national economy, which is about 15%, the investment will also contribute to boost the national economy.